2016
DOI: 10.1074/jbc.m116.730655
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Expression of Human ABO Blood Group Genes Is Dependent upon a Downstream Regulatory Element Functioning through an Epithelial Cell-specific Transcription Factor, Elf5

Abstract: The human ABO blood group system is of great importance in blood transfusion and organ transplantation. The ABO system is composed of complex carbohydrate structures that are biosynthesized by A-and B-transferases encoded by the ABO gene. However, the mechanisms regulating ABO gene expression in epithelial cells remain obscure. On the basis of DNase I-hypersensitive sites in and around ABO in epithelial cells, we prepared reporter plasmid constructs including these sites. Subsequent luciferase assays and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Subsequent plasmid‐based reporter assays indicated a distal regulatory region between +22563 and +22781 relative to the translation start site of ABO , termed the +22.6‐kb site, in KATOIII cells (Fig. A), and the regulatory activity of the region was specific to epithelial cells . Subsequently, we validated the significance of the +22.6‐kb site with use of KATOIII cells with homozygote deletion of the site constructed by the CRISPR/Cas9 system.…”
Section: Regulatory Regions For Abo Expressionmentioning
confidence: 79%
See 3 more Smart Citations
“…Subsequent plasmid‐based reporter assays indicated a distal regulatory region between +22563 and +22781 relative to the translation start site of ABO , termed the +22.6‐kb site, in KATOIII cells (Fig. A), and the regulatory activity of the region was specific to epithelial cells . Subsequently, we validated the significance of the +22.6‐kb site with use of KATOIII cells with homozygote deletion of the site constructed by the CRISPR/Cas9 system.…”
Section: Regulatory Regions For Abo Expressionmentioning
confidence: 79%
“…As shown above, ABO transcription is regulated by the proximal promoter and cell‐specific regulatory regions. However, ABO transcription was not completely lost in the cells with biallelic deletions of the +22.6‐kb site . Also, reporter assays demonstrated transcriptional activity in the DHS region +36.0 (Fig.…”
Section: Prospectmentioning
confidence: 89%
See 2 more Smart Citations
“…It was found that most of the individuals with Bm phenotype were due to the deletion of the whole 5·8‐kb region in the Japanese . Furthermore, some mutations in the 5·8‐kb site were found in the individuals with ABO subtypes, including 23 bp deletion, 5890T>G, 5893G>A, and 5909A>G. These mutations could reduce the erythroid cell‐specific enhancer activity of the 5·8‐kb site and downregulate the transcription of A or B allele .…”
Section: Introductionmentioning
confidence: 99%